Patterns of clinical mentorship in undergraduate nurse education: A comparative case analysis of eleven EU and non-EU countries - Dobrowolska B; McGonagle I; Kane R; Jackson CS; Kegl B; Bergin M; Cabrera E; Cooney Miner D; Di Cara V; Dimoski Z; Kekus D; Pajnkihar M; et al. (Nurse Education Today, 2016)
Background: In spite of the number of studies available in the field and policy documents developed both at the national and the international levels, there is no reliable data available regarding the variation of roles occupied by clinical mentors (CMs) across countries. Objectives: To describe and compare the CM's role; responsibilities; qualifications; employment requirements and experience in undergraduate nurse education as enacted in 11 European Union (EU) and non-EU countries. Design: A case study design. Participants and Setting: A panel of expert nurse educators from 11 countries within and outside of the EU (Croatia, Czech Republic, England, Iceland, Ireland, Italy, Poland, Serbia, Slovenia, Spain, and the USA). Methods: A questionnaire containing both quantitative and qualitative questions was developed and agreed by the panel using a Nominal Group Technique (NGT); four cycles of data collection and analysis were conducted involving key experts in nursing education in each country. Results: In all countries, there are at least two types of clinical mentorship dedicated to undergraduate nursing students: the first is offered by higher education institutions, and the second is offered by health care providers. Variation was noted in terms of profile, responsibilities and professional requirements to act as a CM; however, the CM role is mainly carried out by registered nurses, and in most countries there are no special requirements in terms of education and experience. Those who act as CMs at the bedside continue to manage their usual caseload, thus the role adds to their work burden. Conclusions: Whilst it is imperative to have respect for the different national traditions in undergraduate nurse education, the globalisation of the nursing workforce and greater opportunities for student mobility during the course of their undergraduate education suggests that in areas such as clinical mentorship, jurisdictions, particularly within the EU, should work towards greater system harmonisation.